2021
DOI: 10.1111/tbj.14172
|View full text |Cite
|
Sign up to set email alerts
|

Incidental radiologic findings in breast cancer patients who undergo staging prior to neo‐adjuvant chemotherapy

Abstract: NCCN guidelines discourage the use of staging imaging for newly diagnosed patients with early breast cancer (BC). When performed, incidental radiologic findings of uncertain significance are often encountered. The purpose of this study was to compare incidental findings seen on staging imaging with distant recurrence in patients undergoing neo‐adjuvant chemotherapy (NAC). 396 patients with BC who had NAC from 2008 to 2016 were identified from a prospectively maintained data base. Staging imaging was reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…It is widely recognized that FDG-PET/CT frequently reveals incidental findings. The incidence of these findings depends on patient population and the definition of an incidental finding [ 14 17 , 20 ]. Older patients and patients with malignancies tend to have a higher number of incidental findings on FDG-PET/CT [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely recognized that FDG-PET/CT frequently reveals incidental findings. The incidence of these findings depends on patient population and the definition of an incidental finding [ 14 17 , 20 ]. Older patients and patients with malignancies tend to have a higher number of incidental findings on FDG-PET/CT [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decision to further evaluate an incidental finding depends on patient-specific factors, the level of suspicion associated with the finding and the treating physician’s assessment. In a study conducted by Srour et al, it was reported that 146 out of 262 (55.7%) patients who underwent FDG-PET-CT prior to NAC had incidental findings [ 20 ]. This study included patients with findings deemed “likely” to be physiological, and no further work-up was outlined for these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation